Mobile teaching and learning of coupled-line structures : the multiple-1D coupled-line finite-difference time-domain method - Tan, Eng Leong (2021)
In this article, we present mobile teaching and learning of coupled-line structures using the multiple-1D coupled-line finite-difference time-domain (M1D CL-FDTD) method. The formulation of the M1D CL-FDTD method applicable for CL structures is provided. The method bypasses the more computationally intensive full-wave 3D method, and it is well suited for implementation on mobile devices. Several mobile apps are developed to provide interactive visualization of electromagnetic (EM) wave propagation in CL structures. These visualizations allow the underlying resonating and coupling mechanisms to be elucidated clearly and improve students' understanding of CL theories. Mobile teaching and learning of various CL structures, including coupled transmission lines, CL bandpass filters, directional couplers, and branch-line couplers, are demonstrated and discussed.